Flash Converted Graphene for Ultra‐High Power Supercapacitors. Issue 18 (17th July 2015) - Wang, Lisa J.; El‐Kady, Maher F.; Dubin, Sergey; Hwang, Jee Youn; Shao, Yuanlong; Marsh, Kristofer; McVerry, Brian; Kowal, Matthew D.; Mousavi, Mir F.; Kaner, Richard B.
<x xml:space="preserve">Abstract</x> Supercapacitors are known for their rapid energy charge–discharge properties, often ten to a hundred times faster than batteries. However, there is still a demand for supercapacitors with even faster charge–discharge characteristics to fulfill the requirements of emerging technologies. The power and rate capabilities of supercapacitors are highly dependent on the morphology of their electrode materials. An electrically conductive 3D porous structure possessing a high surface area for ions to access is ideal. Using a flash of light, a method to produce highly interconnected 3D graphene architectures with high surface area and good conductivity is developed. The flash converted graphene is synthesized by reducing freeze‐dried graphene oxide using an ordinary camera flash as a photothermal source. The flash converted graphene is used in coin cell supercapacitors to investigate its electrode materials properties. The electrodes are fabricated using either a precoating flash conversion or a postcoating flash conversion of graphene oxide. Both techniques produce supercapacitors possessing ultra‐high power (5–7 × 105 W kg−1). Furthermore, optimized supercapacitors retain >50% of their capacitance when operated at an ultrahigh current density up to 220 A g−1.